Increasing the efficiency of the inter-branch interactions in the integrated structures of the agro-food sector of Russia - Anna Anfinogentova (European Regional Science Association (ERSA), 2002)
The last decade of development of the Russian economy is characterized by rapid development of new organizational and economic forms emerging on the basis of a complex of inter-connected sectors. The paper studies the theoretical issues of development of the integration processes and proposes the methods of analyzing and forecasting the development of the inter-sector interactions in regional agro-systems. The development of integrated structures in the Russian economy is viewed with reference to the macro- and meso-levels and large production and technological complexes. The authors examine the theoretical and practical aspects of linking into a single system of multi-sector formations as elements of the verti-cally integrated economy and at the same time as inter-firm (corporate) structures. Determined are the prospects of development of the integrated formations with the view to balance the material and financial flows and to eliminate the structural distortions on the food market and in the added value growth. The paper presents the conditions and factors of the re-integration processes in the agro-food complex as a qualitatively new stage of development of the inter-sector interactions. Having studied the institutional trends in the corporate sector of the agro-food complex, the authors determine the criteria of creation of the inte-grated structures, develop the mechanism of increasing their efficiency based on the reduction of transaction costs and the number of intermediates in the food chains. As an instrument of improving the corporate management the authors propose the system of matrix models of integrated structures which is being constructed on the basis of the available statistics, primary accounting data and results of sampling observations. The paper describes the influence of the new forms of inter-sector formations on the structure of the food market. Also it contains the results of the study of the vertical integration processes going in all elements of the food chains as a market access restriction.
Keywords: 330